The Yin and Yang of Human Beta-Defensins in Health and Disease - Weinberg, Aaron; Jin, Ge; Sieg, Scott; McCormick, Thomas S. (Frontiers in Immunology, 2012)
Rapidly evolving research examining the extended role of human beta-defensins (hBDs) in chemoattraction, innate immune-mediated response and promotion of angiogenesis suggest that the collective effects of hBDs extend well beyond their antimicrobial mechanism(s). Indeed, the numerous basic cellular functions associated with hBDs demonstrate that these peptides have dual impact on health, as they may be advantageous under certain conditions, but potentially detrimental in others. The consequences of these functions are reflected in the overexpression of hBDs in diseases, such as psoriasis, and recently the association of hBDs with pro-tumoral signaling. The mechanisms regulating hBD response in health and disease are still being elucidated. Clearly the spectrum of function now attributed to hBD regulation identifies these molecules as important cellular regulators, whose appropriate expression is critical for proper immune surveillance; i.e., expression of hBDs in proximity to areas of cellular dysregulation may inadvertently exacerbate disease progression. Understanding the mechanism(s) that regulate contextual signaling of hBDs is an important area of concentration in our laboratories. Using a combination of immunologic, biochemical and molecular biologic approaches, we have identified signaling pathways associated with hBD promotion of immune homeostasis and have begun to dissect the inappropriate role that beta-defensins may assume in disease.